Ways into the logic of Alexander of Aphrodisias - Flannery, Kevin L. (Philosophia Antiqua, 1995)
Ways into the Logic of Alexander of Aphrodisias is intended to give an overview of the logic of Alexander of Aphrodisias (fl. early Third century A.D.). Since much of what might be called Alexander's logic is simply Aristotelian logic, instead of engaging in point-by-point analysis, it takes up three themes, one from each of the main areas of traditional logic: the assertoric syllogistic, the modal syllogistic, and the area of metalogical concerns. It provides insight not only into Aristotle's logical writings themselves but also into the tradition of scholarship which they spawned: the ideas and analyses of such figures as Theophrastus of Eresus, John Philoponus and (more recently) Jan Lukasiewicz.